Measuring the impact of Wuhan’s COVID-19 lockdown on the growth enterprise market in China - Wang, Li; Huang, Zeyu; Wang, Yanan (Frontiers in Physics, 2023)
The outbreak of COVID-19 had a huge impact on the financial market. As a new growth point in China, it’s necessary to study how SMEs (small and medium-sized enterprises) represented by listed companies on the GEM (growth enterprise market) can withstand sudden shocks. This paper examines the impact of Wuhan’s COVID-19 lockdown on the financial markets based on the data of GEM listed companies and the method of event analysis. The results show that investors had a great response to epidemic related news. Compared with the interest rate cut policy, the targeted RRR reduction policy had a more significant positive influence on the financial markets. Furthermore, in the early stages of COVID-19, there was not a significant effect of distance on the firms’ CARs (cumulative abnormal returns). In an improving epidemic environment, the farther the firms were from Wuhan City, the more positive the impact on their CARs would be. This paper provides new evidence and important enlightenment for preventing the impact of public health emergencies on the GEM market and highlights the significance of developing digital inclusive finance, which can mitigate regional risk and financing issues.